Traditional English Grammar and Beyond N. F. Blake - Wildan Wildan (TEKSTUAL, 2022)
Makalah ini membahas hasil reviuw terhadap buku N.F. Blake yang berjudul Traditional English Grammar and Beyond. Mengingat buku ini sangat kompleks membicarakan tentang linguistik, maka fokus reviuw-nya terbatas pada linguitik tradisonal. Pada prinsipnya, pokok pembahasan yang dibicarakan dalam makalah ini adalah perkembangan awal linguistik tradisional, meliputi zaman Yunani, zaman pertengahan, hingga zaman renaissans. Sebagai hasil reviuw, maka pada reviuw ini juga dikemukakan beberapa kelemahan dan kelebihan linguistik tradisional pada zaman perkembangan awal.This paper discusses the results of the review of the book N.F. Blake entitled Traditional English Grammar and Beyond. Since this book is very complex in discussing linguistics, the focus of the review is limited to traditional linguistics. In principle, the subject discussed in this paper is the early development of traditional linguistics, covering the Greek era, the Middle Ages, to the Renaissance. As a result, this review points out several weaknesses and strengths of traditional linguistics in the early development period.Keywords: Traditional English grammar, N.F.Blake